The effect of house prices on business start-ups: A review and analysis using Swedish regional data - Björn Berggren; Andreas Fili; Mats Håkan Wilhelmsson (REGION, 2017)
Entrepreneurs are at the core of economic development in that they start new businesses or make existing firms grow. To fulfill this important role, entrepreneurs need access to finance. Owing to information asymmetry and the relatively high risk associated with business start-ups, many financiers shy away from engaging in relationships with firms during the early stages of their development. Based on the existing body of knowledge on the financing of entrepreneurship, we know that insider finance is of paramount importance in the early stages of firms’ development. We expand this knowledge base by analyzing the influence of house prices on business start-ups across municipalities in Sweden. In our analysis, we include data from all municipalities in Sweden. Our data on house prices and control variables are collected in period one, and our data on the frequency of start-ups are collected in period two. We find that rising house prices in a municipality lead to a higher frequency of start-ups. In our regression analysis, we find that a 1% increase in house prices leads to a 0.14% increase in start-ups. Our findings are in line with the limited international research that has been previously conducted, and for this reason, they could be seen as a vital addition to the existing body of knowledge within the area of entrepreneurship and regional development.